Nepal-China-India: Prospects and Challenges of Trilateralism - Baral, Bhim Nath (Journal of Political Science, 2019)
Competition and cooperation are the major characters of international system. China and India exactly are in the same position. They are in the race of being global power. They have very bitter experience of relation in the past as both countries fought the war in 1962 and several issues are still unsolved. However, time has come to be global players which is impossible without the support of immediate neighbors. Nepal, though is a small land- locked developing country, is located in strategically important place. A stable and prosperous Nepal can contribute to healthy relation between China and India. In spite of some issues of controversies, there is prospect of trilateral cooperation because of geographical proximity, culture, civilization, trade, investment, transportation tourism and similar other factors. This accounts to the need of joining hands and developing trilateral cooperation. So, this article aims to access the prospects and challenges of trilateralism between China, India and Nepal. The data required are obtained from secondary sources and are descriptive and analytical.